1984
DOI: 10.1002/1097-0142(19840101)53:1<162::aid-cncr2820530128>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis of minute gastric cancer less than 5 mm in diameter

Abstract: When 58 minute gastric cancers less than 5 mm in diameter from 55 patients were classified into 22 of the single group (minute gastric cancer alone) and 36 of the multiple group (associated with other large gastric cancers), the preoperative correct diagnostic rate by x‐ray was 22.7% and 11.1% in the single group and in the multiple group, respectively, with a total rate of 15.5%. The diagnostic rate by endoscopy, aided by endoscopic biopsy, was 95.5%, 13.9%, and 44.8%, respectively. Therefore, it appears that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 2 publications
0
18
1
Order By: Relevance
“…The gastric cancer of less than 5 mm in diameter may be defined as ‘minute gastric cancer’, which can be more easily missed at endoscopy 16 . However, their characteristic endoscopic finding can make endoscopists find cancer 17 . In this study, seven missed lesions of less than 5 mm have no significant histological difference compared with those of more than 5 mm.…”
Section: Discussionmentioning
confidence: 62%
“…The gastric cancer of less than 5 mm in diameter may be defined as ‘minute gastric cancer’, which can be more easily missed at endoscopy 16 . However, their characteristic endoscopic finding can make endoscopists find cancer 17 . In this study, seven missed lesions of less than 5 mm have no significant histological difference compared with those of more than 5 mm.…”
Section: Discussionmentioning
confidence: 62%
“…19 We checked lesions for a moth-eaten appearance with indigo-carmine dye. sex and age) and the endoscopic appearance of lesions (i.e.…”
Section: Endoscopic Evaluationmentioning
confidence: 99%
“…(11,12) Multi-focal gastric cancer is often missed, because they tend to be small and flat in appearance. (13) Our patient developed a satellite lesion 46 months after the initial diagnosis. On review of the images taken in December 2005, no suspicious lesion was identified at the site of the satellite lesion.…”
Section: Discussionmentioning
confidence: 76%